2010
DOI: 10.1677/joe-09-0421
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid modulation of thyroid dual oxidase activity in rats and its impact on thyroid iodine organification

Abstract: The sodium-iodide symporter (NIS) mediates iodide uptake into the thyrocytes, which is important for the diagnosis and therapy of thyroid disorders. Decreased ability to uptake iodide in thyroid carcinomas reduces the efficacy of radioiodine therapy, and retinoic acid (RA) treatment reinduces iodide uptake. The effectiveness of treatment depends not only on iodide uptake but also on the ability of thyrocytes to organify iodine, which is catalyzed by thyroperoxidase (TPO) in the presence of H 2 O 2 . Our goal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
1
13
0
1
Order By: Relevance
“…Thyroids were homogenized in the same buffer, and then centrifuged at 100,000 g for 1h at 4°C. The pellet was suspended in 0.5 ml of 50 mM sodium phosphate buffer, pH 7.2, containing 0.25 M sucrose, 2 mM MgCl 2 , 5 µg/ml aprotinin and 34.8 µg/ml PMSF and stored at -70°C until H 2 O 2 generation measurements [34]. …”
Section: Methodsmentioning
confidence: 99%
“…Thyroids were homogenized in the same buffer, and then centrifuged at 100,000 g for 1h at 4°C. The pellet was suspended in 0.5 ml of 50 mM sodium phosphate buffer, pH 7.2, containing 0.25 M sucrose, 2 mM MgCl 2 , 5 µg/ml aprotinin and 34.8 µg/ml PMSF and stored at -70°C until H 2 O 2 generation measurements [34]. …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, such knowledge in mammalian species is still scarce. While VA impact on thyroid homeostasis has been reported in vivo (Silva et al, 2009; Mühlbauer et al, 2010) and in vitro (Fröhlich et al, 2004), only a recent study suggested that TH signaling might also impact VA signaling/homeostasis (Li et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…The H 2 O 2 generation was quantified in thyroid particulate fractions by the Amplex red/horseradish peroxidase assay (Molecular Probes, Invitrogen, Carlsbad, CA, USA), which detects the accumulation of a fluorescent oxidized product, as previously described. 43 The excised thyroids were processed according to Mühlbauer et al (2010). 44…”
Section: Thyroid H 2 O 2 Productionmentioning
confidence: 99%